Agricultural development and modernization in South Asia - Takeshima, Hiroyuki; Kumar, Anjani; Ahmed, Akhter; Joshi, Pramod Kumar (International Food Policy Research Institute, 2021)
Agriculture, natural resources, and the nutrition landscape in South Asia (SA) are unique. As in other Asian regions, SA’s agriculture is largely smallholder based and continues to employ a large share of the workforce, compared with Latin America. Compared with Africa south of the Sahara (SSA), agricultural modernization and intensification in SA have progressed more substantially. However, compared with East Asia (that is, Northeast and Southeast Asia), the speed of agricultural transformation has remained slower in terms of the exit of labor from farming, despite comparable intensification levels. The region is still home to almost 300 million of the poor, a majority of whom live in rural areas, engaging in agriculture. SA is also one of the regions with the scarcest natural resource endowments per capita, including water resources.1 Finally, the multiple burden of malnutrition persists, as the region remains one of the largest contributors to global undernutrition, while simultaneously overnutrition continues to emerge (Meenaksh 2016). Therefore, in SA, understanding the evolution and implications of agricultural development is important particularly in the context of agricultural transformation, natural resource management, poverty, and food/nutrition security improvement.